ANALISIS DAN PERANCANGAN ANGGARAN BIAYA OVERHEAD PABRIK UNTUK MENINGKATKAN EFESIENSI OPERASIONAL - Narach Larasati Nasution; Imelda Malona Tarigan; Nur Azizaini Zhaharah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research analyzes the management of factory overhead costs (BOP) in increasing the operational efficiency of manufacturing companies. BOP that is not well managed can increase the cost of production and reduce profitability. This research uses a qualitative method with a descriptive approach through interviews, observation and documentation analysis. The research results show that implementing Activity-Based Budgeting (ABB) increases the accuracy of BOP allocations, while Enterprise Resource Planning (ERP) helps transparency and cost monitoring. The main challenge is fluctuating prices of raw materials and energy, which requires budget flexibility. Optimal strategies include indirect labor control, technology-based raw material recording, and energy efficiency. With this strategy, companies can increase operational efficiency, reduce waste, and strengthen competitiveness in the manufacturing industry.